Green Supply Chain Management in Bangladesh's Textile Industry: Driving Environmental, Economic, and Social Sustainability - Md. Miraj Hossain (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Textile industries in Bangladesh are shifting towards a sustainable future, and as a result, many firms are implementing Green Supply chain Management (GSCM). This study aims to evaluate if practicing GSCM in different areas of industry positively impacts environmental, economic, and social performance. Regarding this issue, this paper observes the scopes, drivers, and barriers of practicing GSCM and reviews it. Therefore, the research investigates, through empirical analysis based on responses from 104 textile firms, the influence of GSCM practices on environmental, economic, and social performance. Results confirm that GSCM improves environmental sustainability by reducing emissions, waste, and resource use. It enhances economic performance through cost savings and efficiency gains and also offers several social advantages, improved worker satisfaction, and community engagement. The results bring to light the potential role that GSCM can play in making the textile industry sustainable, along with suggesting policy interventions and further research on longitudinal impacts and advanced technological integration.